2015
DOI: 10.1111/ajo.12404
|View full text |Cite
|
Sign up to set email alerts
|

The influence of mode of birth on neonatal survival and maternal outcomes at extreme prematurity: A retrospective cohort study

Abstract: Mode of birth did not affect neonatal survival or the rate of maternal morbidity for deliveries at 23-26 completed weeks' gestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…If it was not stated in the primary study ( n = 46), we contacted authors to determine outcomes for actively resuscitated infants, by gestational age or birthweight, and information on standard use of antenatal corticosteroids if before the 1994 guidelines (Figure ). We included a total of 15 studies, from the USA (3), France (2), England, Italy, Sweden, Germany, Turkey, Canada, Australia, Trinidad and Tobago, Hungary and Romania, with a total of 12 335 infants (see Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…If it was not stated in the primary study ( n = 46), we contacted authors to determine outcomes for actively resuscitated infants, by gestational age or birthweight, and information on standard use of antenatal corticosteroids if before the 1994 guidelines (Figure ). We included a total of 15 studies, from the USA (3), France (2), England, Italy, Sweden, Germany, Turkey, Canada, Australia, Trinidad and Tobago, Hungary and Romania, with a total of 12 335 infants (see Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…In extremely preterm twins, prior to 1994 and hence advent of antenatal corticosteroid therapy and other advances in neonatal management, some studies had found a decrease in the risk of mortality with caesarean section in second twins weighing 601–999 g [ 66 ] and those weighing less than 1000 g [ 67 ]. More recently, Thomas 2016 [ 68 ] found an increase in survival with caesarean section for multiples from 24 to 26 weeks’ gestation presenting as non-footling breech, but that difference was no longer significant after adjustment for gestational age, chorioamnionitis and maternal age. This study did not stratify data by birth order, and included higher order multiples.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, cohort studies of foetal deliveries before the 26th week of gestation do not indicate that caesarean sections significantly improve the survival of newborns [32,33]. Caesarean sections in pregnancies before 26 weeks have been shown to be a risk factor for complications in subsequent pregnancies.…”
Section: Non-cephalic Fetal Presentationmentioning
confidence: 99%